THE INFLUENCE OF HEADMASTERâS SUPERVISION AND ACHIEVEMENT MOTIVATION ON EFFECTIVE TEACHERS - Renata, Renata; Wardiah, Dessy; Kristiawan, Muhammad (Jurnal Dosen Universitas PGRI Palembang)
Abstract: This study aimed at examining 1) the influence of headmasterâs supervision on effective teachers, 2) the influence of achievement motivationÂ on effective teachers, and 3) the influence of headmasterâs supervision and achievement motivation on effective teachers. This research used quantitative. Data were analyzed using multiple linear regression formula SPSS (Statistical Product and Service Solution) version 16.0 for windows. This study showed 1) there was significant influence of headmasterâs supervision on effective teachers with tobtained 2,452 and ttable was 1,980; 2) there was significant influence of achievement motivation on effective teachers with tobtained 5,627 and ttable was 1,980, and 3) there was significant influence of headmasterâs supervision and achievement motivation on effective teachers with fobtained 23.618 and ftable was 3,267. This research contributed to the Headmaster should upgrade the supervision of teachers and achievement motivation where they would actualized the effective teachers.Â Index Terms: Headmasterâs Supervision, Achievement Motivation, Effective Teachers.